Retaining Quranic memorisation for huffaz at the Malaysian tertiary institutions: Key challenges and future IoT potentialities - Fatimah Zaharah, Ismail; Mohamed Fathy, Mohamed Abdelgelil; Najmiah, Omar; Nor Hafizi, Yusof; Rahimah, Embong; Ahmad Farimin, Ahmad Osman (2019)
The transformation of tahfiz al-Quran (Quranic preservation) education in Malaysia has produced innumerable secondary school huffaz (those who have committed the Quran to memory) who would be entering tertiary institutions to further their studies in various professional field. In the institutions, they would not have anyone to guide them on the Quran besides having freedom to organise their daily activities. They would be busy with academic matters, not having a conducive environment for retaining the memorisation and frequently face time management problems. The question is how far the huffaz at the tertiary education level are capable of retaining the memorisation of al-Quran. Therefore, this paper aims to identify challenges faced by the huffaz at the tertiary institutions and IoT potentialities that could be adopted in efforts to retain the memorisation. This study is qualitative in nature and used the content analysis approach, which employed the document analysis method, while the data were analysed thematically. This study had identified five main issues that were presumed to be problems for the huffaz in retaining their memorisation of al-Quran. Besides that, this study propose three main IoT ecosystem that would support the huffaz at the tertiary education level when doing revision or murajaah of the Quran.